(untitled) (Bulletin of Pure and Applied Sciences – Physics, 2022)
In the present study, effects of next to next-nearest-neighbor (NNNN) hopping of d electrons in the crystal of mixed valence compounds has been discussed. For convenient theoretical calculation and computer simulation within exact diagonalization method, a small cluster of eight lattice sites is considered here to investigate the valence transition through the study of the inter-site and on-site f-d correlation functions. Unusual magnetic behavior of mixed valence compounds has also been examined. Antiferromagnetic (AF) order has been developed in the compounds of rare earth elements with the addition of NNNN hopping interaction within the extended Falicov-Kimball model. The extrapolation of the curves of the reciprocal susceptibility (χ-1) intercept at a negative temperature which confirms AF order in the system.